Tackling moisture stress with drought-tolerant potato (Solanum tuberosum) varieties: Perception of Karnataka farmers - RANA, RAJESH K; SHARMA, NEERAJ; ARYA, S; SINGH, B P; KADIAN, M S; CHATURVEDI, RAHUL; PANDEY, S K (The Indian Journal of Agricultural Sciences, 2013)
Karnataka plays an imperative role of supplying processing grade potatoes to Indian processing industry duringSeptember and December months when there is dearth of raw material. Heat and moisture stress aggravate existing grimpotato husbandry outlook due to shallow and carbon deficit soils, small and fragmented land holdings, and resourcepaucity of farmers in the area. Lack of technological support may prove to be a threat to sustainability of potato farmingand growth of Indian potato processing industry. With this objective into consideration, current study was undertakenunder the broader project â€œEnhanced Food and Income Security in South West and Central Asia through Potato Varieties with Improved Tolerance to Abiotic Stressâ€. Farmersâ€™ opinions on yield enhancing attributes on their farms, good and bad characters of the existing potato varieties and reasons for the abandonment potato varieties were collected and analyzed. Priority indices of farmersâ€™ opinion on desirable attributes were computed and based on these indices top ten attributes were listed and supplied to the crop improvement team of the project. The research paper also describes some important areas where development agencies need to act sooner than later for ensuring welfare of potato farmers and crop in the area.